toner
Patent Information
- Application Number
- JP2021080709
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-05-12
Smart Images

Figure 0007631086000008 
Figure 0007631086000001 
Figure 0007631086000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a toner used in electrophotography, electrostatic recording, electrostatic printing, and the like. [Background technology]
[0002] In recent years, as full-color electrophotographic copiers have become more widespread, there is a demand for additional performance improvements, such as increased speed and higher image quality, energy saving performance, shorter recovery time from sleep mode, and compatibility with a wide variety of media.
[0003] Specifically, the printing market is now demanding high speed, high image quality, and high productivity while being compatible with a wide range of media (paper types). For example, even when the paper type is changed from thick paper to thin paper, media uniformity is required, which allows printing to continue without changing the process speed or the heating temperature setting of the fixing device according to the paper type. From the viewpoint of obtaining excellent media uniformity, the toner is required to complete proper fixing in a wide temperature range from low to high. Therefore, Patent Document 1 proposes a method of using crosslinked particles in a toner binder to improve fixing separation.
[0004] On the other hand, there is also a demand for providing high-quality images for various media. When outputting image data captured by digital cameras, digital video cameras, mobile terminals, etc., or graphic images such as posters, high-gloss paper such as coated paper or art paper is used. When an image is output on such high-gloss media, if the gloss of the image is low compared to the paper gloss, the image will have a sunken impression, and the image quality and texture will be impaired. Therefore, for such applications, it is necessary to form a high-gloss image. Therefore, Patent Document 2 proposes a toner to which a crystalline resin is added to improve gloss.
[0005] Furthermore, as a toner capable of shortening the recovery time from a sleep state, a toner with excellent charge retention properties and with little change in charge amount over a long period of sleep state is required. Therefore, Patent Document 3 proposes a toner in which the molecular mobility of a crystalline resin is suppressed and which exhibits excellent charge retention properties. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2011-034013 A [Patent Document 2] JP 2014-032242 A [Patent Document 3] JP 2019-219640 A Summary of the Invention [Problem to be solved by the invention]
[0007] The toner described in Patent Document 1 exhibits strain hardening during large deformation such as at the exit of the fixing nip, increasing the viscosity and reducing the contact area with the fixing film, which allows for improved fixing separation. However, increasing the crosslink density of the toner and increasing the viscosity of the toner can cause unevenness to form on the surface of the fixed image, resulting in reduced gloss.
[0008] On the other hand, the toner described in Patent Document 2 can achieve high and stable gloss over a wide temperature range by controlling the melting speed of the crystalline resin. However, since the crystalline resin has a lower volume resistivity than the amorphous resin, it is prone to charge leakage. Therefore, a toner using a crystalline resin as a binder resin may have poor charge retention.
[0009] In addition, the toner described in Patent Document 3 can exhibit excellent charge retention because the molecular mobility of the crystalline resin is suppressed. However, when a crystalline resin in which two or more monomer units with significantly different polarities are polymerized in a block form is used, the crystalline resin and the wax tend to be compatible with each other, and the exudation of the wax during fixing tends to be suppressed. Therefore, the fixing separation property may be poor.
[0010] For the above reasons, it has been difficult to satisfy all of the requirements for fixation separation, high gloss, and charge retention. Therefore, there is an urgent need to develop a toner that exhibits excellent fixation separation even on thin coated paper in addition to exhibiting excellent gloss and charge retention. The present disclosure provides a toner that exhibits excellent fixation separation even on thin coated paper in addition to exhibiting excellent gloss and charge retention. [Means for solving the problem]
[0011] The present disclosure provides a toner having toner particles containing a binder resin and a water-soluble polyvalent metal salt, The main component of the binder resin is a polyester resin, The acid value of the polyester resin is 1.0 mgKOH / g or more and 30.0 mgKOH / g or less, the polyvalent metal in the water-soluble polyvalent metal salt is at least one metal selected from the group consisting of Mg, Ca, Al, Fe, and Zn; the water-soluble polyvalent metal salt is a chloride, a nitrate or a sulfate of the polyvalent metal; The water-soluble polyvalent metal salt has a solubility in water at 25° C. of 30 g / 100 mL or more and 200 g / 100 mL or less, In a cross-sectional observation of the toner using a transmission electron microscope, it was found that 0.002 μm 2 More than 0.050μm 2 the ratio of the area of the domain derived from the water-soluble polyvalent metal salt having the following area is 80 area % or more and 100 area % or less, The toner satisfies the following formula (1), where At (area %) is the ratio of the total area of the domains derived from the water-soluble polyvalent metal salt to the total area of the cross section of the toner particle, and Fm (atomic %) is the ratio of the polyvalent metal atoms to the atoms detected by fluorescent X-ray analysis of the toner. 0.02≦At / Fm≦0.10 (1) Effect of the Invention
[0012] The present disclosure can provide a toner that exhibits excellent gloss and charge retention, and also exhibits excellent fixing separation properties even on thin coated paper. [Brief description of the drawings]
[0013] [Figure 1] An example of the measurement results of the strain stress profile of toner during heating DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In the present disclosure, the description of "XX or more and YY or less" or "XX to YY" representing a numerical range means a numerical range including the lower and upper limits which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. Furthermore, a monomer unit refers to a reacted form of a monomer substance in a polymer. Furthermore, a crystalline resin is a resin in which an endothermic peak is observed in differential scanning calorimetry (DSC).
[0015] The present disclosure relates to a toner having toner particles containing a binder resin and a water-soluble polyvalent metal salt. So, The main component of the binder resin is a polyester resin, The acid value of the polyester resin is 1.0 mgKOH / g or more and 30.0 mgKOH / g or less, the polyvalent metal in the water-soluble polyvalent metal salt is at least one metal selected from the group consisting of Mg, Ca, Al, Fe, and Zn; the water-soluble polyvalent metal salt is a chloride, a nitrate or a sulfate of the polyvalent metal; The water-soluble polyvalent metal salt has a solubility in water at 25° C. of 30 g / 100 mL or more and 200 g / 100 mL or less, In a cross-sectional observation of the toner using a transmission electron microscope, it was found that 0.002 μm 2 More than 0.050μm 2 the ratio of the area of the domain derived from the water-soluble polyvalent metal salt having the following area is 80 area % or more and 100 area % or less, The toner satisfies the following formula (1), where At (area %) is the ratio of the total area of the domains derived from the water-soluble polyvalent metal salt to the total area of the cross section of the toner particle, and Fm (atomic %) is the ratio of the polyvalent metal atoms to the atoms detected by fluorescent X-ray analysis of the toner. 0.02≦At / Fm≦0.10 (1)
[0016] The present inventors have been studying a toner having excellent gloss and charge retention, and excellent fixing separation properties. As shown in Patent Document 1, if the entire toner is strongly crosslinked to improve the fixing separation properties, the viscosity of the toner increases, and unevenness is formed on the surface of the fixed image, making it impossible to achieve both high gloss and fixing separation properties. Therefore, the present inventors have considered that it is important to crosslink locally, rather than strongly crosslinking the entire toner.
[0017] However, when inorganic fine particles are added as a local crosslink, the resin around the inorganic fine particles becomes hard, but not sufficiently, and when the toner is stretched after passing through the fixing nip, strain hardening does not occur. Therefore, the present inventors considered that it is important to locally and strongly crosslink the binder resin in the toner, and focused on water-soluble metal salts as a material for locally and strongly crosslinking the binder resin. As a result, the present inventors found that a desired toner can be obtained by using a water-soluble metal salt to control the crosslinking state between the polyester resin, which is the binder resin, and the water-soluble metal salt.
[0018] Specifically, by using a water-soluble metal salt, moisture is adsorbed on the surface of the metal salt, which easily induces dissociation of ions, and the affinity with the acidic polar group of the binder resin can be increased, improving the fixing separation property. Furthermore, it has been found that by making the water-soluble metal salt exist as a domain in the toner, local crosslinking is realized, and a toner that maintains high gloss and has excellent fixing separation property can be obtained. Furthermore, it has been found that by making the acidic polar group of the polyester resin and the metal ion of the water-soluble polyvalent metal salt locally crosslinked in the toner, a toner that has excellent gloss and fixing separation property can be obtained without decreasing the charge retention property.
[0019] First, the water-soluble polyvalent metal salt will be described. The polyvalent metal of the water-soluble polyvalent metal salt is at least one metal selected from the group consisting of Mg, Ca, Al, Fe, and Zn. The polyvalent metal is thought to crosslink with the acidic polar groups in the molecular chains of multiple polyester resins, so that the molecular chains of the polyester resin become dense around the metal ions of the polyvalent metal. As a result, strong interactions and intermolecular forces can be generated, resulting in excellent fixing and separating properties.
[0020] Furthermore, since the metal ions of the above polyvalent metals have a large ionic radius relative to the acidic polar group of the polyester resin, strong local crosslinking can be realized and high gloss can be maintained. The polyvalent metal in the water-soluble polyvalent metal salt is selected from the group consisting of Mg, Ca, Al, Fe and Zn. The polyvalent metal is preferably at least one selected from the group consisting of Mg, Ca, and Al.
[0021] The water-soluble polyvalent metal salt is at least one selected from the group consisting of chlorides, nitrates, and sulfates of polyvalent metals. Such water-soluble polyvalent metal salts have low interaction with resin components, so that the water-soluble polyvalent metal salt can be present locally in the toner. The water-soluble polyvalent metal locally crosslinks with the acidic polar group of the polyester resin in the toner to form domains, thereby maintaining high gloss. In particular, the water-soluble polyvalent metal salt is more preferably a sulfate of a polyvalent metal.
[0022] The water-soluble polyvalent metal salt has a solubility in water at 25°C of 30 g / 100 mL or more and 200 g / 100 mL or less. The acidic polar group of the polyester resin and the metal ion of the water-soluble polyvalent metal salt crosslink with each other, increasing the toner viscosity and providing excellent fixing and separating properties. Furthermore, by using a highly water-soluble metal salt with a solubility in water of 30 g / 100 mL or more, moisture is adsorbed on the surface of the metal salt, which makes it easier to induce dissociation of the ions. As a result, the affinity with the acidic polar group of the polyester resin can be increased, providing excellent fixing and separating properties. On the other hand, by using a metal salt with a solubility of 200 g / 100 mL or less, moisture absorption in a high-temperature and high-humidity environment can be suppressed, and charge retention can be improved.
[0023] In addition, the solubility of the water-soluble multivalent metal salt in water at 25°C is preferably 50g / 100mL or more. This makes it easier to induce ion dissociation due to adsorption of moisture on the metal salt surface, thereby improving the fixing separation property. In addition, the solubility of the water-soluble multivalent metal salt in water at 25°C is preferably 150g / 100mL or less, and more preferably 100g / 100mL or less. This makes it possible to suppress the hygroscopicity in a high-temperature and high-humidity environment, and improves the charge retention property.
[0024] The toner particles contain a binder resin and a water-soluble polyvalent metal salt. The binder resin is mainly composed of a polyester resin. The polyester resin is preferably an amorphous polyester resin. The main component means that the content is 50% by mass or more. The content of the polyester resin in the binder resin is preferably 70% by mass to 100% by mass, more preferably 80% by mass to 100% by mass, even more preferably 90% by mass to 100% by mass, and even more preferably 95% by mass to 100% by mass. The binder resin may contain other resins in addition to the polyester resin to the extent that the above effect is not impaired. As the other resins, the following polymers and the like can be used.
[0025] Examples of such resins include homopolymers of styrene and its substitutes, such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene-(meth)acrylic copolymer resins, such as styrene-p-chlorostyrene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-acrylic acid ester copolymer, and styrene-methacrylic acid ester copolymer, polyester resins, and hybrid resins in which polyester resins and styrene-(meth)acrylic copolymer resins are mixed or in which both are partially reacted; polyvinyl chloride, phenolic resins, natural resin-modified phenolic resins, natural resin-modified maleic acid resins, acrylic resins, methacrylic resins, polyvinyl acetate, silicone resins, polyester resins, polyurethane resins, polyamide resins, furan resins, epoxy resins, xylene resins, polyethylene resins, and polypropylene resins.
[0026] Examples of polyester resins include the following condensation polymers. The polyester resin is preferably a condensation polymer of a polyhydric alcohol (dihydric, trihydric or higher alcohol) and a polyvalent carboxylic acid (dihydric, trihydric or higher carboxylic acid), an acid anhydride thereof, or a lower alkyl ester thereof.
[0027] Here, when preparing a branched polymer, it is preferable to partially crosslink within the molecule of the polyester resin. For this purpose, it is preferable to use a polyfunctional compound having a valence of 3 or more. Therefore, it is preferable to include a trivalent or more carboxylic acid, its acid anhydride or its lower alkyl ester, and / or a trivalent or more alcohol as a raw material monomer for the polyester resin. That is, the polyester resin is more preferably a condensation polymer of a divalent alcohol, a divalent carboxylic acid, its acid anhydride or its lower alkyl ester, and a trivalent or more carboxylic acid, its acid anhydride or its lower alkyl ester. The trivalent or more carboxylic acid preferably includes a trivalent carboxylic acid and a tetravalent carboxylic acid.
[0028] The following polyhydric alcohol monomers can be used as the polyhydric alcohol monomers of the polyester resin: Dihydric alcohol components include, for example, ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, hydrogenated bisphenol A, and bisphenol represented by formula (A) and its derivatives; [ka]
[0029] (In the formula, R is an ethylene or propylene group, x and y are each an integer of 0 or more, and the average value of x+y is 0 or more and 10 or less.) Examples of the diols include those represented by the formula (B). [ka]
[0030] Examples of trihydric or higher alcohol components include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene. Among these, glycerol, trimethylolpropane, and pentaerythritol are preferably used. These dihydric alcohols and trihydric or higher alcohols can be used alone or in combination.
[0031] As the polybasic carboxylic acid monomer of the polyester resin, the following polybasic carboxylic acid monomers can be used. As the dibasic carboxylic acid component, for example, maleic acid, fumaric acid, Acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid, n-dodecylsuccinic acid, isododecylsuccinic acid, n-octenylsuccinic acid, n-octylsuccinic acid, isooctylsuccinic acid, isooctylsuccinic acid, anhydrides of these acids, and lower alkyl esters thereof. Of these, maleic acid, fumaric acid, terephthalic acid, and n-dodecenylsuccinic acid are preferably used.
[0032] Examples of trivalent or higher carboxylic acids, their anhydrides or their lower alkyl esters include 1,2,4-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, their anhydrides or their lower alkyl esters. Among these, 1,2,4-benzenetricarboxylic acid, i.e., trimellitic acid or its derivatives, is particularly preferred because it is inexpensive and easy to control the reaction. These divalent carboxylic acids and trivalent or higher carboxylic acids can be used alone or in combination.
[0033] As the trivalent or higher carboxylic acid, the following tetravalent carboxylic acids are preferred from the viewpoint of facilitating the formation of crosslinking points: 1,1,2,2-ethanetetracarboxylic acid, 1,1,1,2-ethanetetracarboxylic acid, 1,1,3,3-polypanetetracarboxylic acid, 1,1,2,3-propanetetracarboxylic acid, 1,1,2,2-propanetetracarboxylic acid, 2-(carboxymethyl)propane-1,1,3-tricarboxylic acid, 1,1,4,4-butanetetracarboxylic acid, 1,1,2,4-butanetetracarboxylic acid, 1,1,3,4-butanetetracarboxylic acid, 1,1,2,2-butanetetracarboxylic acid, 1,1,3,3-butanetetracarbo tetracarboxylic acid, 2,2,3,3-butanetetracarboxylic acid, 1,2,3,4-cyclobutanetetracarboxylic acid, 1,1,5,5-pentanetetracarboxylic acid, 1,1,4,5-pentanetetracarboxylic acid, 1,1,3,5-pentanetetracarboxylic acid, 1,1,2,5-pentanetetracarboxylic acid, 1,1,4,4-pentanetetracarboxylic acid, 1,1,3,4-pentanetetracarboxylic acid, 1,1,2,4-pentanetetracarboxylic acid, 1,1,3,3-pentanetetracarboxylic acid, 1,1,2,3-pentanetetracarbo carboxylic acid, 1,1,2,2-pentanetetracarboxylic acid, 1,2,3,4-pentanetetracarboxylic acid, 1,2,3,5-pentanetetracarboxylic acid, 3-(carboxymethyl)butane-1,1,4-tricarboxylic acid, 2-(carboxymethyl)butane-1,1,4-tricarboxylic acid, 2-methylbutane-1,1,4,4-tetracarboxylic acid, 1,1,6,6-hexanetetracarboxylic acid, 1,1,5,6-hexanetetracarboxylic acid, 1,2,3,4-hexanetetracarboxylic acid, 1,2,3,5-hexanetetracarboxylic acid carboxylic acid, 1,2,3,6-hexanetetracarboxylic acid, 2-methylpentane-1,1,5,5-tetracarboxylic acid, 3-methylpentane-1,1,5,5-tetracarboxylic acid, 2,3-dimethylbutane-1,1,4,4-tetracarboxylic acid, 1,1,7,7-heptanetetracarboxylic acid, 1,1,8,8-octanetetracarboxylic acid, 1,1,9,9-nonanetetracarboxylic acid, 1,1,10,10-decanetetracarboxylic acid, 3,5-bis(carboxymethyl)-3,4,4,5-tetramethylheptanedioic acid, and the like.
[0034] Among them, it is preferable to use 3,5-bis(carboxymethyl)-3,4,4,5-tetramethylheptanedioic acid. The content of monomer units polymerized from trivalent or higher (preferably trivalent and tetravalent, more preferably tetravalent) carboxylic acids among the constituent components of the polyester resin is preferably 1.0 to 10.0 mol %, more preferably 1.5 to 5.0 mol %, and even more preferably 2.0 to 4.0 mol %. In addition, the polyester resin Among the constituent components, the content of monomer units formed by polymerization of trivalent or higher (preferably trivalent and tetravalent, more preferably tetravalent) carboxylic acids is preferably 1.0 to 20.0 mass%, more preferably 2.0 to 10.0 mass%, and even more preferably 3.0 to 8.0 mass%.
[0035] The method for producing the polyester resin is not particularly limited, and a known method can be used. For example, the above-mentioned alcohol monomer and carboxylic acid monomer are simultaneously charged, and polymerized through an esterification reaction or an ester exchange reaction and a condensation reaction to produce the polyester resin. The polymerization temperature is not particularly limited, but is preferably in the range of 180°C to 290°C. For the polymerization of the polyester resin, for example, a polymerization catalyst such as a titanium-based catalyst, a tin-based catalyst, zinc acetate, antimony trioxide, or germanium dioxide can be used. In particular, the polyester resin is more preferably a polyester resin polymerized using a tin-based catalyst.
[0036] The acid value of the polyester resin is 1.0 mgKOH / g or more and 30.0 mgKOH / g or less. When the acid value is 1.0 mgKOH / g or more, the acidic polar group of the polyester resin and the metal ion of the water-soluble polyvalent metal salt are crosslinked, the toner viscosity can be increased, and excellent fixing separation properties can be obtained. When the acid value is 30.0 mgKOH / g or less, the moisture absorption in a high-temperature and high-humidity environment can be suppressed, and the charge retention can be improved.
[0037] In addition, the acid value of the polyester resin is preferably 5.0 mgKOH / g or more. This increases the number of crosslinking points between the acidic polar group of the polyester resin and the metal ion of the water-soluble high metal salt, improving the fixing separation property. In addition, the acid value of the polyester resin is preferably 25.0 mgKOH / g or less. This can suppress the moisture absorption in a high temperature and high humidity environment, improving the charge retention property. More preferably, it is 8.0 mgKOH / g or more and 15.0 mgKOH / g or less.
[0038] In cross-sectional observation of the toner using a transmission electron microscope (TEM), it was found that the area of the domains derived from water-soluble polyvalent metal salts was less than 0.002 μm 2 More than 0.050μm 2 The proportion of the area of the domain derived from the water-soluble polyvalent metal salt having the following area is 80 area % or more and 100 area % or less.
[0039] The domain derived from the water-soluble polyvalent metal salt is a domain formed by cross-linking the acidic polar group of the polyester resin with the metal ion of the water-soluble polyvalent metal salt. The domain can be distinguished by binarizing the cross-section of the toner by a specific threshold value using the image processing software "ImageJ" in TEM observation. The specific procedure will be described later.
[0040] When the area ratio of the domain is within the above range, the acidic polar group of the polyester resin and the metal ion of the water-soluble multivalent metal salt are crosslinked, the toner viscosity can be increased, and excellent fixing separation properties can be obtained. Furthermore, when the acidic polar group of the polyester resin and the metal ion of the water-soluble multivalent metal salt are crosslinked locally in the toner, high gloss can be maintained.
[0041] In order to show excellent fixing separation properties, it is necessary for the acidic polar group of the polyester resin and the metal ion of the water-soluble multivalent metal salt to crosslink and increase the toner viscosity. Therefore, it is necessary that the domains derived from the water-soluble multivalent metal salt are not too large, are dispersed to a certain extent, and the acidic polar group of the polyester resin and the metal ion of the water-soluble multivalent metal salt are crosslinked. Therefore, it is necessary to have an area of 0.050 μm2 It is essential to form a domain derived from the following water-soluble polyvalent metal salt.
[0042] In order to achieve excellent gloss, it is necessary to locally crosslink the acidic polar group of the polyester resin and the metal ion of the water-soluble multivalent metal salt in the toner. Therefore, it is necessary for the domain derived from the water-soluble multivalent metal salt to be localized to some extent to form a domain, and for the acidic polar group of the polyester resin and the metal ion of the water-soluble multivalent metal salt to be crosslinked. Therefore, it is necessary to form a domain having an area of 0.002 μm 2 It is essential to form a domain derived from the above water-soluble polyvalent metal salt.
[0043] And this 0.002μm 2 More than 0.050μm 2 The area ratio of the domain derived from the water-soluble polyvalent metal salt having the following area must be 80 area % or more and 100 area % or less of the total area of the domain. This allows the acidic polar group of the polyester resin to crosslink with the metal ion of the water-soluble high metal salt, increasing the toner viscosity, and further allows the acidic polar group of the polyester resin to crosslink locally with the metal ion of the water-soluble polyvalent metal salt in the toner, improving both the fixing separation property and the gloss.
[0044] In addition, 0.002 μm 2 More than 0.050μm 2 The area ratio of the domain derived from the water-soluble polyvalent metal salt having the following area is preferably 90 area % or more and 100 area % or less, and more preferably 95 area % or more and 100 area % or less, of the total area of the domain. This allows the binder resin to be strongly crosslinked locally, and improves both the fixing separation property and the gloss property.
[0045] The following methods can be used to make domains originating from the water-soluble polyvalent metal salt exist on the cross section of the toner particles. Since the water-soluble polyvalent metal salt does not disperse in the toner particles based on ion size and needs to form domains, a dry toner manufacturing method is preferably used. For example, a method can be used in which a water-soluble polyvalent metal salt is added during toner manufacturing by a pulverization method, and a domain is formed during melt kneading.
[0046] In the pulverization method, the domain can be controlled by adjusting the temperature and residence time of melt kneading. The temperature of melt kneading is preferably 100° C. or higher and 160° C. or lower, and more preferably 120° C. or higher and 140° C. or lower. The residence time during melt kneading is preferably 30 to 100 seconds, and more preferably 45 to 75 seconds. The area of the domain can be increased by lowering the melt-kneading temperature, and can be decreased by increasing the melt-kneading temperature. The area of the domain can also be controlled by the residence time of the melt-kneading. The area of the domain can be increased by increasing the residence time of the melt-kneading, and can be decreased by decreasing the residence time of the melt-kneading.
[0047] In addition, when a cross-section of a toner particle is observed using a transmission electron microscope, the ratio of the total area of the domains derived from a water-soluble polyvalent metal salt to the total area of the cross-section of the toner particle is defined as At (area %), and the ratio of the polyvalent metal atoms to the atoms detected by X-ray fluorescence analysis (XRF) of the toner is defined as Fm (atomic %), and the following formula (1) is satisfied. 0.02≦At / Fm≦0.10 (1)
[0048] Satisfying the above formula (1) indicates that the proportion of metal salts forming domains derived from the water-soluble multivalent metal salt is high among all the water-soluble multivalent metal salts contained in the toner. As a result, in the toner, the acidic polar group of the polyester resin and the metal ion of the water-soluble multivalent metal salt are locally crosslinked to form domains, so that the macroscopic viscosity of the toner can be controlled low and high gloss can be maintained. When At / Fm is less than 0.02, the crosslinks become fine and uniform, resulting in a decrease in gloss. In addition, when At / Fm is 0.10 or less, the domains can be uniformly dispersed in the toner, and the toner viscosity can be increased, improving the fixing separation property.
[0049] In addition, it is preferable that the following formula (2) is satisfied. 0.04≦At / Fm≦0.09 (2) Satisfying the above formula (2) indicates that the ratio of metal salts forming domains derived from water-soluble multivalent metal salts is higher among all water-soluble multivalent metal salts contained in the toner. Therefore, metal ions can be locally crosslinked, further improving gloss. Fixing separation properties are also improved. At / Fm can be increased by increasing the residence time of melt kneading, and can be decreased by shortening the residence time of melt kneading.
[0050] At (area %) is preferably 0.1 to 6.0, more preferably 0.2 to 0.8. Fm (atomic %) is preferably 1.0 to 75.0, more preferably 3.0 to 15.0.
[0051] When observing the cross section of a toner particle using a transmission electron microscope (TEM), it was found that only 0.002 μm 2 More than 0.050μm 2The area ratio of the domain derived from the water-soluble polyvalent metal salt having the following area is preferably 0.10 area% or more and 5.00 area% or less, and more preferably 0.25 area% or more and 2.00 area% or less. When the above area ratio is 0.10 area% or more, the crosslinking points between the acidic polar group of the polyester resin and the metal ion of the water-soluble high metal salt become more sufficient, so that the fixing separation property is further improved. On the other hand, when the above area ratio is 5.00 area% or less, the crosslinking points between the acidic polar group of the polyester resin and the metal ion of the water-soluble polyvalent metal salt are prevented from becoming too many, so that the gloss is further improved.
[0052] Of the total area of a toner particle, 0.002 μm 2 More than 0.050μm 2 The ratio of the area of the domain derived from the water-soluble polyvalent metal salt having the following area can be set to 0.10 area % or more and 5.00 area % or less by the following methods. For example, a water-soluble polyvalent metal salt is added during toner production by a pulverization method, and the melt-kneading temperature and residence time are adjusted. The melt-kneading temperature is preferably 100°C to 160°C.
[0053] In addition, in the strain stress profile of the toner at 95°C, the stress at 200% strain is preferably 20 kPa or more and 40 kPa or less, more preferably 22 kPa or more and 32 kPa or less. After the toner passes through the fixing nip, it is stretched the most at about 200%. Therefore, in the strain stress profile of the toner at 95°C, when the stress at 200% strain is 20 kPa or more and 40 kPa or less, it indicates that the acidic polar group of the polyester resin and the metal ion of the water-soluble polyvalent metal salt have crosslinking points locally, and the stress against the strain of the toner at high temperatures is of appropriate strength. As a result, better fixing separation property and gloss are obtained.
[0054] As a means for adjusting the stress to 20 kPa or more and 40 kPa or less, for example, a method of adding a water-soluble polyvalent metal salt during toner production by a pulverization method and adjusting the temperature and residence time of melt kneading may be mentioned.
[0055] Furthermore, when the acid value of the polyester resin is 5.0 mgKOH / g or more and 25.0 mgKOH / g or less, and the polyvalent metal of the water-soluble polyvalent metal salt is at least one selected from the group consisting of Mg, Ca, Al, Fe, and Zn, the stress can be easily adjusted to 20 kPa or more and 40 kPa or less.
[0056] A preferred toner composition is described in detail below. [wax] The toner particles may contain wax. Examples of the wax include the following. Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; Oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; Waxes whose main component is fatty acid esters, such as carnauba wax; Deoxidized carnauba wax and other fatty acid esters that have been partially or completely deoxidized.
[0057] Among these, from the viewpoint of low-temperature fixing property and hot offset resistance of the toner, hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and fatty acid ester waxes such as carnauba wax are preferred.
[0058] From the viewpoint of toner fixing and separating property, a hydrocarbon wax is more preferable. The content of the wax in the toner particles is preferably 1.0 part by mass or more and 20.0 parts by mass or less with respect to 100 parts by mass of the binder resin. When the content of the wax is in the above range, the hot offset resistance at high temperatures is further improved.
[0059] From the viewpoint of achieving both storage stability and hot offset resistance of the toner, it is preferable that the peak temperature of the maximum endothermic peak of the toner satisfies the following: In other words, in an endothermic curve during temperature rise measured by a differential scanning calorimeter (DSC), the peak temperature of the maximum endothermic peak present in the temperature range of 30° C. to 200° C. is preferably 50° C. to 110° C.
[0060] [Coloring agent] The toner particles may contain a colorant as necessary. Examples of the colorant include the following. Examples of the black colorant include carbon black; and a colorant toned to black using a yellow colorant, a magenta colorant, and a cyan colorant. As the colorant, a pigment may be used alone, or a dye and a pigment may be used in combination. From the viewpoint of the image quality of a full-color image, it is preferable to use a dye and a pigment in combination.
[0061] Magenta toner pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35.
[0062] Dyes for magenta toners include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.
[0063] Pigments for cyan toner include: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45, a copper phthalocyanine pigment with 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton. An example of a dye for cyan toners is CI Solvent Blue 70.
[0064] Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow toner dyes include CI Solvent Yellow 162.
[0065] These colorants can be used alone or in mixture, or in the form of a solid solution. The colorant is selected in terms of hue angle, chroma, brightness, light resistance, OHP transparency, and dispersibility in toner particles. The content of the colorant is preferably 0.1 to 30.0 parts by mass relative to 100 parts by mass of the binder resin.
[0066] [Charge control agent] The toner particles may contain a charge control agent as necessary. By blending a charge control agent, the charge characteristics can be stabilized, and the amount of triboelectric charge can be optimally controlled according to the development system. As the charge control agent, a known one can be used, but in particular, a metal compound of an aromatic carboxylic acid is preferred, which is colorless, has a high charging speed of the toner, and can stably maintain a constant amount of charge.
[0067] Examples of negative charge control agents include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes.
[0068] The charge control agent may be added internally or externally to the toner particles. The content of the charge control agent is preferably 0.2 parts by mass to 10.0 parts by mass, and more preferably 0.5 parts by mass to 10.0 parts by mass, based on 100 parts by mass of the binder resin.
[0069] [Inorganic fine particles] The toner may contain inorganic fine particles as an external additive as necessary. Examples of inorganic fine particles include silica fine particles, titanium oxide fine particles, alumina fine particles, and composite oxide fine particles thereof. Among inorganic fine particles, silica fine particles and titanium oxide fine particles are preferred for improving flowability and uniform charging. The inorganic fine particles are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof.
[0070] From the viewpoint of improving fluidity, inorganic fine particles as external additives should have a specific surface area of 50 m 2 / g~400m 2 From the viewpoint of improving durability and stability, it is preferable that the inorganic fine particles as the external additive have a specific surface area of 10 m 2 / g~50m 2In order to achieve both improved fluidity and durability and stability, inorganic fine particles having a specific surface area within the above range may be used in combination.
[0071] The content of the external additive is preferably 0.1 parts by mass to 10.0 parts by mass with respect to 100 parts by mass of the toner particles. The toner particles and the external additive can be mixed using a known mixer such as a Henschel mixer.
[0072] [Developer] The toner can be used as a one-component developer, but in order to further improve dot reproducibility and provide stable images over a long period of time, it is preferable to mix the toner with a magnetic carrier and use it as a two-component developer.
[0073] Examples of magnetic carriers that can be used include commonly known magnetic carriers such as iron oxide; metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, chromium, and rare earth elements, alloy particles thereof, and oxide particles thereof; magnetic materials such as ferrite; and magnetic material-dispersed resin carriers (so-called resin carriers) that contain a magnetic material and a binder resin that holds the magnetic material in a dispersed state.
[0074] When the toner is mixed with a magnetic carrier to be used as a two-component developer, the mixing ratio of the magnetic carrier is preferably 2% by mass to 15% by mass, and more preferably 4% by mass to 13% by mass, in terms of the toner concentration in the two-component developer.
[0075] [Method of manufacturing toner particles] The toner particles can be manufactured by a known method for manufacturing toner particles, such as a melt-kneading method, an emulsion aggregation method, or a dissolution suspension method. The procedure for manufacturing toner particles by the pulverization method will be described below. In the pulverization method, the materials for the toner particles are melt-kneaded and pulverized to obtain toner particles. The temperature for melt-kneading is preferably 100°C to 160°C, and more preferably 118°C to 142°C.
[0076] In the raw material mixing process, materials constituting the toner particles, such as binder resin and water-soluble polyvalent metal salt, and other components such as wax, colorant, charge control agent, etc. as required, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include double con mixers, V-type mixers, drum mixers, super mixers, Henschel mixers, Nauta mixers, and Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.).
[0077] Next, the mixed materials are melt-kneaded to disperse the materials in the binder resin. In the melt-kneading process, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used, and single-screw or twin-screw extruders are mainstream due to their advantage of being capable of continuous production. For example, a KTK type twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM type twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned. Furthermore, the resin composition obtained by melt-kneading may be rolled with two rolls or the like and cooled with water or the like in a cooling process.
[0078] The cooled resin composition is then pulverized to a desired particle size in a pulverization process. In the pulverization process, the resin composition is coarsely pulverized using a pulverizer such as a crusher, a hammer mill, or a feather mill. The resin composition is then finely pulverized using a pulverizer such as a Cryptron System (Kawasaki Heavy Industries), a Super Rotor (Nisshin Engineering), a Turbo Mill (Turbo Kogyo), or an air jet type pulverizer.
[0079] Thereafter, as necessary, the mixture is classified using a classifier or sieve such as an inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), or a Faculty (manufactured by Hosokawa Micron Corporation).
[0080] The obtained toner particles may be used as they are as a toner. If necessary, an external additive may be added to the surface of the toner particles to obtain a toner. As a method for adding an external additive, a method for adding an external additive may be used. The toner thus obtained is mixed with a predetermined amount of various known external additives, and the resulting mixture is stirred and mixed using a mixing device such as a double con mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation) as an external additive machine.
[0081] The methods for measuring various physical properties are described below. [Measurement of resin acid value] The acid value is the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1 g of a sample. The acid value of the binder resin is measured in accordance with JIS K 0070-1992, and specifically, is measured according to the following procedure.
[0082] (1) Preparation of reagents Dissolve 1.0 g of phenolphthalein in 90 mL of ethyl alcohol (95% by volume), add ion-exchanged water to make 100 mL, and obtain a phenolphthalein solution. Dissolve 7 g of special grade potassium hydroxide in 5 mL of water, and add ethyl alcohol (95% by volume) to make 1 L. Place in an alkali-resistant container to avoid contact with carbon dioxide, etc., leave for 3 days, and then filter to obtain a potassium hydroxide solution. Store the obtained potassium hydroxide solution in an alkali-resistant container. The factor of the potassium hydroxide solution is obtained by placing 25 mL of 0.1 mol / L hydrochloric acid in an Erlenmeyer flask, adding several drops of the phenolphthalein solution, and titrating with the potassium hydroxide solution, and then calculating from the amount of the potassium hydroxide solution required for neutralization. The 0.1 mol / L hydrochloric acid used is prepared in accordance with JIS K 8001-1998.
[0083] (2) Operation (A) Main Test Weigh out 2.0 g of sample into a 200 mL Erlenmeyer flask, add 100 mL of a toluene / ethanol (2:1) mixed solution, and dissolve for 5 hours. Next, add a few drops of the phenolphthalein solution as an indicator, and titrate with the potassium hydroxide solution. The end point of the titration is when the indicator remains a light red color for about 30 seconds. (B) Blank test The titration is carried out in the same manner as above, except that no sample is used (i.e., only the toluene / ethanol (2:1) mixed solution is used).
[0084] (3) The obtained result is substituted into the following formula to calculate the acid value. A = [(CB) × f × 5.61] / S Here, A is the acid value (mgKOH / g), B is the amount of potassium hydroxide solution added for the blank test (mL), C is the amount of potassium hydroxide solution added for the main test (mL), f is the factor of the potassium hydroxide solution, and S is the mass of the sample (g).
[0085] [Separation of polyester resin from toner] By utilizing the difference in solubility of each material contained in the toner in a solvent, each material can be separated from the toner. First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23°C, and the soluble matter (amorphous polyester) is separated from the insoluble matter (crystalline polyester, release agent, colorant, inorganic fine particles, etc.). Second separation: The insoluble matter obtained in the first separation (crystalline polyester, release agent, colorant, inorganic fine particles, etc.) is dissolved in MEK at 100°C, and the soluble matter (crystalline polyester, release agent) is separated from the insoluble matter (colorant, inorganic fine particles, etc.). Third separation: The soluble matter (crystalline polyester, release agent) obtained in the second separation is dissolved in chloroform at 23°C, and the soluble matter (crystalline polyester) and the insoluble matter (release agent) are separated.
[0086] [Solubility measurement] The solubility in water at 25°C is measured by measuring the amount (g) of a water-soluble polyvalent metal salt that dissolves in 100 mL of water kept at 25°C.
[0087] [Cross-section observation of toner] First, the toner is thoroughly dispersed in a photocurable epoxy resin, and then the epoxy resin is cured by irradiating it with ultraviolet light. The resulting cured product is cut using a microtome equipped with a diamond blade to prepare a thin sample with a thickness of 100 nm. The sample is then stained with ruthenium tetroxide, and the cross section of the toner is then observed using a transmission electron microscope (TEM) (product name: electron microscope Tecnai TF20XT, manufactured by FEI) at an acceleration voltage of 120 kV. Observe the toner particle to obtain a TEM image. In this case, the cross section of the toner particle is selected to have a major axis diameter that is 0.9 to 1.1 times the number average particle diameter (D1) of the toner particles measured according to the method for measuring the number average particle diameter (D1) of the toner particles described later.
[0088] The domains derived from the water-soluble multivalent metal salts are extracted from the observed image by binarizing it using the image processing software "ImageJ" (available from https: / / imagej.nih.gov / ij / ) as follows: Select "Image-Adjust-Threshold" from the observed image, set the threshold in the displayed dialogue box so that the entire cross section of the toner particle is extracted, and binarize it. The same image is binarized using the same procedure, but by changing only the threshold, so that only the domains derived from the water-soluble multivalent metal salts are extracted. Specifically, the threshold is set to 120 / 255 levels to extract the domains. The domains observed using the above settings are deemed to be domains derived from the water-soluble multivalent metal salts.
[0089] In the binarized image, [Analyze-Analyze Particle] , set the area of the domain to 0.002 μm 2 More than 0.050μm 2The sum of the areas of the following domains is calculated. The area can be measured using image processing software "Image-Pro Plus (manufactured by Media Cybernetics)". The area of the toner particles and the total area of the domains originating from the water-soluble multivalent metal salt present on the cross section of the toner particles are also calculated. From the calculated values, the proportion At (area %) of the total area of the domains originating from the water-soluble multivalent metal salt to the total area of the cross section of the toner particles, and the area of the domains originating from the water-soluble multivalent metal salt that is less than 0.002 μm 2 More than 0.050μm 2 The area ratio of the following domains is calculated by observing 100 toner particles and using the arithmetic mean value.
[0090] [X-ray fluorescence analysis (XRF)] The measurement of the fluorescent X-rays of each element conforms to JIS K 0119-1969, but is specifically as follows. The measurement equipment used is a wavelength dispersive X-ray fluorescence analyzer "Axios" (PANalytical) and the accompanying dedicated software "SuperQ ver.4.0F" (PANalytical) for setting measurement conditions and analyzing measurement data. Rh is used as the anode of the X-ray tube, the measurement atmosphere is vacuum, the measurement diameter (collimator mask diameter) is 27 mm, and the measurement time is 10 seconds. In addition, a proportional counter (PC) is used to measure light elements, and a scintillation counter (SC) is used to measure heavy elements.
[0091] To prepare the measurement sample, the toner is placed inside a special aluminum ring for pressing, flattened, and then compressed at 20 MPa for 60 seconds using a tablet molding compression machine "BRE-32" (manufactured by Maekawa Test Machinery Manufacturing Co., Ltd.) to form a pellet with a thickness of approximately 2 mm and a diameter of approximately 39 mm.
[0092] Measurements are performed under the above conditions, and elements are identified based on the peak positions of the obtained X-rays. The concentration is calculated from the counting rate (unit: cps), which is the number of X-ray photons per unit time. The calculation formula is as follows: As shown below. Proportion of polyvalent metal atoms to atoms in toner Fm [atomic%] = (content of polyvalent metal atoms in toner [kcps]) / (content of atoms in toner [kcps]) × 100
[0093] In X-ray fluorescence analysis, calibration curves are created using an X-ray fluorescence analyzer using oxide particles with known elemental contents, and the content of each element in the composite oxide particles is determined using these calibration curves.
[0094] [Identification of water-soluble polyvalent metal salts contained in toner] The toner is dissolved in chloroform at 23°C. Water is added, and the mixture is thoroughly stirred and allowed to stand before being separated. The water phase obtained is subjected to X-ray fluorescence analysis to identify the water-soluble polyvalent metal salt contained in the toner. Based on the identified water-soluble polyvalent metal salt, the above-mentioned Fm analysis and solubility measurement are performed.
[0095] [Method for measuring the strain stress profile of toner at 95°C] The measurement device used is a precision universal testing machine "Autograph AG-X" (manufactured by Shimadzu Corporation). The measurement sample is prepared by placing 0.5 g of toner in a dedicated aluminum ring for pressing, flattening it, and pressing it for 1 minute at 20 MPa using a tablet molding compression machine "BRE-32" (manufactured by Maekawa Test Machinery Manufacturing Co., Ltd.) to form a pellet with a thickness of approximately 2 mm and a width of approximately 6 mm.
[0096] Measurements are performed under conditions of a tensile speed of 210 mm / min, a chuck distance of 7 mm, and a measurement temperature of 95°C, to obtain a strain-stress profile as shown in Figure 1. From the obtained strain-stress profile, the stress at a strain of 200% is calculated. EXAMPLES
[0097] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. In the following formulations, the parts are by weight unless otherwise specified.
[0098] [Example 1] <Production Example of Amorphous Resin A1> Polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane: 29.7 parts (0.07 moles; 40.0 mol% based on the total number of moles of polyhydric alcohol) Polyoxyethylene (2.2)-2,2-bis(4-hydroxyphenyl)propane: 40.8 parts (0.13 moles; 60.0 mol% based on the total number of moles of polyhydric alcohol) Terephthalic acid: 30.4 parts (0.195 moles; 97.5 mol% based on the total number of moles of polycarboxylic acids) 3,5-bis(carboxymethyl)-3,4,4,5-tetramethylheptanedioic acid (D1): 1.66 parts (0.005 moles; 2.37 mole% based on the total number of moles of polycarboxylic acids) The above materials were put into a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. Then, 1.0 part of tin 2-ethylhexanoate (esterification catalyst) was added as a catalyst to 100 parts of the total amount of monomers. Next, the atmosphere in the flask was replaced with nitrogen gas, and the temperature was gradually raised while stirring, and the reaction was carried out for 2.5 hours while stirring at a temperature of 200°C. Furthermore, the pressure in the reaction vessel was reduced to 8.3 kPa, and after maintaining it for 1 hour, it was cooled to 180°C and returned to atmospheric pressure (first reaction step). Trimellitic anhydride: 0.04 parts (0.0002 moles; 0.13 mol% based on the total number of moles of polycarboxylic acids) tert-Butylcatechol (polymerization inhibitor): 0.1 parts After that, the above materials were added, the pressure in the reactor was reduced to 8.3 kPa, and the temperature was maintained at 160°C. The reaction was allowed to proceed for 15 hours, and the softening point of the reaction mixture was measured according to ASTM D36-86. After it was confirmed that the temperature had reached 95°C, the temperature was lowered to stop the reaction (second reaction step). In this way, amorphous resin A1, which is an amorphous polyester resin, was obtained. The obtained amorphous resin A1 had a softening point (Tm) of 98°C and an acid value of 11.3 mgKOH / g.
[0099] <Production Examples of Amorphous Resins A2 to A5> Amorphous resins A2 to A5 were obtained in the same manner as in the production example of amorphous resin A1, except that the types and amounts of the polyhydric alcohol monomer and the polybasic carboxylic acid monomer were changed to those shown in Table 1. The physical properties of the obtained amorphous resins are shown in Table 1.
[0100] <Toner 1 Manufacturing Example> Amorphous resin A1: 100.0 parts Fischer-Tropsch wax (maximum endothermic peak temperature 90°C): 5.0 parts Carbon black: 10.0 parts Magnesium sulfate: 1.5 parts The above materials were mixed at a rotation speed of 1500 rpm for 5 min using a Henschel mixer (FM-75, manufactured by Mitsui Mining Co., Ltd.), and then kneaded at an average residence time of 60 seconds using a twin-screw kneader (PCM-30, manufactured by Ikegai Co., Ltd.) set at a temperature of 130°C. The kneaded material obtained was cooled and coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed material. The coarsely crushed material obtained was finely crushed using a mechanical crusher (T-250, manufactured by Turbo Kogyo Co., Ltd.). Furthermore, classification was performed using a Faculty (F-300, manufactured by Hosokawa Micron Corporation), and toner particles 1 were obtained. The operating conditions were a classification rotor rotation speed of 11000 rpm and a dispersion rotor rotation speed of 7200 rpm.
[0101] Toner particles: 100 parts Silica microparticle A: Fumed silica surface-treated with hexamethyldisilazane (Median diameter (D50) based on number is 120 nm): 4 parts Small inorganic particles: Titanium oxide particles surface-treated with isobutyltrimethoxysilane (Median diameter (D50) based on number is 10 nm): 1 part The above materials were mixed in a Henschel mixer (FM-75, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) at a rotation speed of 1900 rpm for a rotation time of 10 minutes to obtain Toner 1 exhibiting negative charging properties.
[0102] <Production Examples of Toners 2 to 31> Toners 2 to 31 were obtained in the same manner as in Production Example 1 of Toner 1, except that the type of amorphous resin A, the type and amount of water-soluble polyvalent metal salt added, and the kneading temperature were changed as shown in Table 2. The obtained physical properties are shown in Table 3.
[0103] <Magnetic Carrier 1 Manufacturing Example> Number average particle size: 0.30μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 1 Number average particle size: 0.50μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 2 To 100 parts of each of the above materials, 4.0 parts of a silane compound (3-(2-aminoethylaminopropyl)trimethoxysilane) was added, and the mixture was mixed and stirred at high speed in a container at 100° C. or higher to treat each of the fine particles. Phenol: 10% by weight Formaldehyde solution: 6% by weight (Formaldehyde 40% by mass, methanol 10% by mass, water 50% by mass) Magnetite treated with the above silane compound 1: 58% by mass Magnetite 2 treated with the above silane compound: 26% by mass 100 parts of the above material, 5 parts of 28% by mass ammonia aqueous solution, and 20 parts of water were placed in a flask, and the temperature was raised to 85°C in 30 minutes while stirring and mixing, and the mixture was held for 3 hours to polymerize and harden the resulting phenolic resin. The hardened phenolic resin was then cooled to 30°C, and water was added, after which the supernatant liquid was removed, and the precipitate was washed with water and then air-dried. This was then dried at a temperature of 60°C under reduced pressure (5 mmHg or less) to obtain a spherical magnetic carrier 1 with magnetic material dispersion. The 50% particle size (D50) based on volume was 34.21 μm.
[0104] <Production example of two-component developer 1> 92.0 parts of magnetic carrier 1 and 8.0 parts of toner 1 were mixed in a V-type mixer (V-20, manufactured by Seishin Enterprise Co., Ltd.) to obtain two-component developer 1.
[0105] <Production Examples of Two-Component Developers 2 to 31> In the production example of two-component developer 1, the same operation was carried out except for the changes shown in Table 4, to obtain two-component developers 2 to 31.
[0106] [evaluation] The evaluation was carried out using the above-mentioned two-component developer 1. A modified Canon imageRUNNER ADVANCE C5560 digital commercial printing printer was used as the image forming apparatus, and two-component developer 1 was placed in the black developing device. The modifications to the apparatus included the fixing temperature, process speed, and DC voltage V of the developer carrier. DC , the charging voltage of the electrostatic latent image carrier V D The laser power and the laser power can be freely set. The image output evaluation is performed by outputting a FFh image (solid image) with the desired image ratio, and adjusting the V so that the amount of toner on the FFh image on the paper is as desired. DC , V D The evaluation described below was performed by adjusting the laser power and the color level. FFh is a value obtained by expressing 256 gradations in hexadecimal, with 00h being the first gradation (white background) of the 256 gradations and FFh being the 256th gradation (solid background) of the 256 gradations. Evaluation was performed based on the following evaluation method, and the results are shown in Table 5.
[0107] <Fixing and separation performance of thin paper in high temperature and humidity environment> Using the above modified copier, a 4.0 mm margin was provided at the top edge, and the toner loading amount was 1.20 mg / cm 2 A full-surface solid image of 100 mm was produced without being fixed. Next, the unfixed image was fixed at a process speed of 348 mm / sec using a modified fixing machine. The fixing separation property was evaluated by increasing the fixing temperature from 100°C by 5°C increments, and the temperature at which wrapping occurred was lowered by 5°C, which was taken as the fixing separation temperature. The test environment was a high temperature and high humidity environment (30°C / 80% RH). The transfer material for the fixed image was an A4 size Pearl Coat N (73 g / m 2 ) (Mitsubishi Paper Mills, Ltd.) was used. Grades C and above were considered to be good. (Evaluation Criteria) A: The fixing separation temperature exceeds 150°C. B: Fixing separation temperature is 150℃ C: Fixing separation temperature is 145℃ D: Fixing separation temperature is 140°C or less
[0108] <Glossiness> Using the modified copier, the toner loading amount was 0.45 mg / cm 2 A full-surface solid image of 1000 g / m2 was prepared without being fixed. Next, the unfixed image was fixed by a modified fixing machine at a process speed of 348 mm / sec and a fixing temperature of 195° C. The transfer material for the fixed image was A4-size Mondi color copy paper (300.0 g / m2). 2 ) (Mondi) was used. For the images among the above fixed images in which no hot offset occurred, a handy gloss meter PG-3D (manufactured by Nippon Denshoku Industries Co., Ltd.) was used to measure the average value of three arbitrary points on each image under the condition of a light incidence angle of 60°, and this was taken as the gloss value. The evaluation results are shown in Table 3. A grade of C or higher was judged to be good. (Evaluation Criteria) A: Gross value is 20 or more B: Gross value is 15 or more and less than 20 C: Gloss value is 10 or more and less than 15 D: Gloss value is less than 10
[0109] <Charge retention rate under high temperature and high humidity conditions> Paper: GFC-081 (81.0g / m 2 ) (Canon Marketing Japan Inc.) Toner load on paper: 0.35mg / cm 2 (The DC voltage of the developer carrier V DC , the charging voltage of the electrostatic latent image carrier V D , and adjusted by laser power) Evaluation image: A 2cm x 5cm image placed in the center of the A4 paper. Fixing test environment: High temperature and humidity environment: Temperature 30℃ / Humidity 80%RH (hereinafter referred to as "H / H") Process speed: 377mm / sec
[0110] The toner on the electrostatic latent image carrier was collected by suction using a metal cylinder and a cylindrical filter, and the amount of triboelectric charge of the toner was calculated. Specifically, the amount of triboelectric charge of the toner on the electrostatic latent image carrier was measured using a Faraday Cage. A Faraday Cage is a coaxial double cylinder, with the inner and outer cylinders insulated. If a charged body with a charge Q is placed inside the inner cylinder, electrostatic induction will result in the same effect as if a metal cylinder with a charge Q exists. The amount of induced charge was measured using an electrometer (Kessley 6517A, Kessley), and the amount of charge Q (mC) divided by the mass M (kg) of the toner in the inner cylinder (Q / M) was determined as the amount of triboelectric charge of the toner. Triboelectric charge of toner (mC / kg)=Q / M
[0111] First, the above evaluation image was formed on the electrostatic latent image carrier, and before it was transferred to the intermediate transfer body, the rotation of the electrostatic latent image carrier was stopped, and the toner on the electrostatic latent image carrier was sucked and collected using a metal cylindrical tube and a cylindrical filter, and [initial Q / M] was measured. Subsequently, the developer was left in the evaluation machine in a H / H environment for two weeks, and then the same operation as before leaving it was performed to measure the charge amount Q / M (mC / kg) per unit mass on the electrostatic latent image carrier after leaving it. The above initial Q / M per unit mass on the electrostatic latent image carrier was set to 100%, and the maintenance rate of Q / M per unit mass on the electrostatic latent image carrier after leaving it ([Q / M after leaving it] / [initial Q / M]×100) was calculated and judged according to the following criteria. C or higher was judged to be good. (Evaluation Criteria) A: Retention rate is 95.0% or higher B: Retention rate is 90.0% or more but less than 95.0% C: Retention rate is between 85.0% and 90.0% D: Retention rate is less than 85.0%
[0112] <Examples 2 to 23 and Comparative Examples 1 to 8> Evaluations were performed in the same manner as in Example 1, except that two-component developers 2 to 23 were used as Examples 2 to 23, and two-component developers 24 to 31 were used as Comparative Examples 1 to 8. The evaluation results are shown in Table 5.
[0113] [Table 1] In the table, the unit of acid value is mgKOH / g. The abbreviations are as follows: BPA-PO: Bisphenol A propylene oxide adduct BPA-EO: Bisphenol A ethylene oxide adduct TPA: Terephthalic acid D1: 3,5-bis(carboxymethyl)-3,4,4,5-tetramethylheptanedioic acid D2: 1,1,6,6-hexanetetracarboxylic acid TMA anhydride: Trimellitic anhydride
[0114] [Table 2] In the table, the unit of acid value is mgKOH / g, and the unit of solubility is g / 100 mL of water at 25°C.
[0115] [Table 3] In the table, At is the ratio (area %) of the total area of the domains derived from the water-soluble polyvalent metal salt to the total area of the cross section of the toner particle, and Fm is the ratio (atomic %) of the polyvalent metal atoms to the atoms detected by fluorescent X-ray analysis of the toner. The area % is the ratio of the total area of the cross section of the toner particle to the total area of the cross section of the toner particle within 0.002 μm 2 More than 0.050μm 2 It is the ratio of the area of the domain derived from the water-soluble polyvalent metal salt having the following area: The strain stress is the stress (kPa) at 200% strain in the strain stress profile of the toner at 95°C.
[0116] [Table 4]
[0117] [Table 5]
Claims
1. A toner having toner particles containing a binder resin and a water-soluble polyvalent metal salt, The main component of the binder resin is a polyester resin, The acid value of the polyester resin is 1.0 mgKOH / g or more and 30.0 mgKOH / g or less, the polyvalent metal in the water-soluble polyvalent metal salt is at least one metal selected from the group consisting of Mg, Ca, Al, Fe, and Zn; the water-soluble polyvalent metal salt is a chloride, a nitrate or a sulfate of the polyvalent metal; The water-soluble polyvalent metal salt has a solubility in water at 25° C. of 30 g / 100 mL or more and 200 g / 100 mL or less, In a cross-sectional observation of the toner using a transmission electron microscope, it was found that 0.002 μm 2 0.050 μm or more 2 the ratio of the area of the domain derived from the water-soluble polyvalent metal salt having the following area is 80 area % or more and 100 area % or less, A toner characterized in that, when the ratio of the total area of the domains derived from the water-soluble polyvalent metal salt to the total area of the cross section of the toner particle is At (area %), and the ratio of the polyvalent metal atoms to the atoms detected by fluorescent X-ray analysis of the toner is Fm (atomic %), the following formula (1) is satisfied: 0.02≦At / Fm≦0.10 (1)
2. In a cross-sectional observation of the toner using a transmission electron microscope, it was found that the area of the toner particles was less than 0.002 μm 2 0.050 μm or more 2 2. The toner according to claim 1, wherein the proportion of an area of a domain derived from the water-soluble polyvalent metal salt having an area below is 0.10 area % or more and 5.00 area % or less.
3. 3. The toner according to claim 1, wherein in a strain stress profile of the toner at 95[deg.] C., the stress at a strain of 200% is 20 kPa or more and 40 kPa or less.
4. 4. The toner according to claim 1, wherein the polyvalent metal in the water-soluble polyvalent metal salt is at least one selected from the group consisting of Mg, Ca, and Al.
5. 5. The toner according to claim 1, wherein the water-soluble polyvalent metal salt is a sulfate of the polyvalent metal.
6. 6. The toner according to claim 1, wherein the acid value of the polyester resin is from 5.0 mgKOH / g to 25.0 mgKOH / g.
7. 0.002 μm 2 0.050 μm or more 2 7. The toner according to claim 1, wherein an area ratio of the domains derived from the water-soluble multivalent metal salt having an area below is 90 area % or more and 100 area % or less of a total area of the domains derived from the water-soluble multivalent metal salt.
Citation Information
Patent Citations
Toner for static charge developer
JP1980166651A
Toner and toner production method
JP2011034013A
toner
JP2014032242A
Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method
JP2019144437A
Toner and method for manufacturing toner
JP2019219640A